The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.jhh.1002140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valsartan addition to amlodipine on ankle oedema and subcutaneous tissue pressure in hypertensive patients

Abstract: The aim of this study was to assess the effect of valsartan addition to amlodipine on ankle foot volume (AFV) and pretibial subcutaneous tissue pressure (PSTP), two objective measures of ankle oedema. After a 4-week placebo period, 80 grade 1-2 hypertensive patients (diastolic blood pressure (DBP)490 mm Hg and o110 systolic blood pressure (SBP)4140 mm Hg) were randomized to amlodipine 10 mg or valsartan 160 mg or amlodipine 10 mg plus valsartan 160 mg for 6 weeks according to an open-label, blinded end point, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 22 publications
6
71
0
3
Order By: Relevance
“…5 In an additional study, the incidence rate of peripheral oedema was lower with valsartan and amlodipine in combination (5.4%) than with amlodipine monotherapy (8.7%). 6 Moreover, in the trials summarized in Table 1 that recorded the highest incidences of oedema in CCB monotherapy-treated patients, addition of an ACEI or an ARB to the daily therapeutic regimen (benazepril 10 mg added to amlodipine 5 mg; 16 valsartan 160 mg added to amlodipine 10 mg 17 ) reduced the incidence of ankle oedema significantly.…”
Section: Mitigation Of Ccb-induced Oedemamentioning
confidence: 99%
See 3 more Smart Citations
“…5 In an additional study, the incidence rate of peripheral oedema was lower with valsartan and amlodipine in combination (5.4%) than with amlodipine monotherapy (8.7%). 6 Moreover, in the trials summarized in Table 1 that recorded the highest incidences of oedema in CCB monotherapy-treated patients, addition of an ACEI or an ARB to the daily therapeutic regimen (benazepril 10 mg added to amlodipine 5 mg; 16 valsartan 160 mg added to amlodipine 10 mg 17 ) reduced the incidence of ankle oedema significantly.…”
Section: Mitigation Of Ccb-induced Oedemamentioning
confidence: 99%
“…10,12,22 This theoretical concept is borne out by the results of individual clinical trials that have shown that the incidence of oedema is substantially lower in patients who receive ACEI/ CCB or ARB/CCB combination therapy than in those treated with CCB monotherapy. 6,[15][16][17][18][19][20][21][22] Moreover, a meta-analysis of 82 studies that compared the safety and efficacy of benazepril/amlodipine therapy with that of nine monotherapy regimens concluded that this combination was associated with a lower overall rate of side effects and of side effects that led to withdrawal than either amlodipine or nifedipine monotherapy. Table 1 shows the rates of oedema from eight relevant clinical trials.…”
Section: Mitigation Of Ccb-induced Oedemamentioning
confidence: 99%
See 2 more Smart Citations
“…76 However, few trials have been designed to test the effect of specific antihypertensive combinations on cardiovascular or renal end points. [77][78][79][80][81] Dual RAS/CCB blockade would seem a propitious combination, since these classes of antihypertensive agents target multiple mechanisms involved in hypertensive vascular disease progression.…”
Section: Dual Calcium Channel/ras Blockadementioning
confidence: 99%